A rediscovered beveled osseous rod: Clarification of the archaeological record. (2nd January 2022) - Kornfeld, Marcel; Holen, Kathleen; Holen, Steven
Abstract : Elongated osseous implements, often referred to as osseous or bone rods, are a defining characteristic of Early Paleoindian cultures of North America. A rod found in the Lindenmeier collection at the Denver Museum of Nature & Science, was radiocarbon dated and the results published several years ago, demonstrating its Mid Paleoindian association. The specimen highlighted the importance of museum collections for furthering our knowledge of rare items of the past. Subsequently, the "Lindenmeier" rod was found to be from a different location, the Hell Gap site. In this paper we trace the rod's history to correct the archaeological record and discuss its place within variations among osseous rods.